Crystal structure of dichlorido-bis(4-chlorophenyl-κC 1)(2,2′-bipyridyl-κ 2 N,N′)tin(IV), C22H16Cl4N2Sn - Lo, Kong Mun *; Lee, See Mun *; Tiekink, Edward R. T. * (De Gruyter Open [Commercial Publisher], 2021)
C22H16Cl4N2Sn, monoclinic, P21/n (no. 14), a = 10.0393(1) Å, b = 14.4490(2) Å, c = 14.1502(2) Å, β = 92.846(1)°, V = 2050.07(5) Å3, Z=4, Rgt(F) = 0.0224, wRref (F2) = 0.0590, T = 100 K.